1995
DOI: 10.1063/1.358782
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport in (100)CoSi2/Si contacts

Abstract: A detailed investigation of the electrical transport in (100) CoSi,/Si contacts is presented. The transport properties of epitaxial CoSiZ films, obtained both by ion-beam synthesis and by solid-state reaction of a Ti/Co bimetallic layer, are compared with the transport properties of conventional polycrystalline CoSi, layers. The electrical resistivity, the magnetoresistance, and the Hall effect are measured on Hall bars for temperatures ranging from 1.2 to 300 K and magnetic fields up to 5 T. Very high values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…However, it has been found that the sheet resistance of titanium silicide may increase significantly as the line width decreases [5]. Recently, academic interest has focused on the CoSi 2 and NiSi compounds due to their low resistivity, high-temperature stability, compatibility for self-aligned process, and self passivating nature in an oxygen-rich environment [6][7][8]. For CoSi 2 , the gate sheet resistance may increase at very narrow width due to the thinning of CoSi 2 films at the edge of polysilicon line.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…However, it has been found that the sheet resistance of titanium silicide may increase significantly as the line width decreases [5]. Recently, academic interest has focused on the CoSi 2 and NiSi compounds due to their low resistivity, high-temperature stability, compatibility for self-aligned process, and self passivating nature in an oxygen-rich environment [6][7][8]. For CoSi 2 , the gate sheet resistance may increase at very narrow width due to the thinning of CoSi 2 films at the edge of polysilicon line.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Cobalt disilicide is the material of choice primarily because of its low-electrical resistivity as well as having a very small lattice mismatch with Si and a high degree of chemical and thermal stability. [6][7][8][9][10][11][12][13][14] Consistent with recent trends of miniaturization of microelectronic devices, the interface contact layer must be well defined in size, thickness, and crystalline perfection on an atomic scale. Scanning tunneling microscopy ͑STM͒ and transmission electron microscopy ͑TEM͒ are two very effective techniques of determining the degree of control.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally the specific resistance of CoSi 2 is low and buried circuits may be produced ͑3D integration͒. 1,2 Furthermore, CoSi 2 layers open the possibility to design new devices like permeable base transistors, metal base transitors, or vertical ultrafast photodetectors. 3 These applications require almost perfect layers.…”
Section: Introductionmentioning
confidence: 99%